Rancang Bangung Sistem Informasi Penjadwalan Produksi PT.Bukit Baja Anugrah - Muzdalifah, Chafida; Widodo, Arifin Puji; Setyawan, Henry Bambang (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
PT. Bukit Baja Anugrah is a company engaged in the manufacturing of pipes. Currently in production activities often experience delays in the fulfillment of customer demand for products pipeline. his is due to the absence of production schedules at every process of production, so that the buildup of production and lead to delayed product that will be in production. Based on the existing problems, then made a production scheduling information system by using EDD (earlist Due Date) and methods of SPT (Shortest prosecing Time). The scheduling information system are the order process, the process of calculation methods, the process of determining the best method, and the process of making the product schedule. This system can provide scheduling according to the calculation method using the criteria of the method of EDD (earlist Due Date) and methods of SPT (Shortest prosecing Time). he criteria used are: average completion time - price, utilization, job number average - average and delay - average. And the provision of appropriate weight value prosentanse PT.Bukit Baja Anugrah The information system generates the scheduling process and machinery products, and generate reports - reports related to reports presentanse most ordered products, product scheduling reports, report scheduling engine, report production plans, production schedules reports period and production scheduling reports day